Measurement of Optical Density of Blood with Varying Time Using UV-Vis Spectroscopic Method - Srinivasan, S.; Ponnambalam, U.; Gunasekaran, S. (Asian Journal of Chemistry, 2010)
The object of the present work is to measure and study the optical density of blood at various stipulated periods of time using ultraviolet and visible spectroscopic method. SL 159 single beam UV-Vis spectrophotometer was used to record the spectra in the wavelength range between 200 and 700 nm. There are six wavelength maxima exhibited at 215, 280, 346, 418, 544 and 578 nm corresponding to proteins, amino acids, NADH and NADPH, CO-hemoglobin respectively in blood. From the study it is observed that optical density of blood constituents decreases with time except CO-hemoglobin which occurs at the wavelength at 418 nm.